2019
DOI: 10.5267/j.msl.2019.1.013
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship and organizational performance: Empirical insight into the role of entrepreneurial training, culture and government funding across higher education institutions in Pakistan

Abstract: This paper examines the relationship between entrepreneurial training, entrepreneurial culture and organizational performance. Accordingly, the study also investigates the moderating effect of government funding on the relationship between entrepreneurial culture, entrepreneurial training and business performance among the public universities in Pakistan. The respondents include 415 heads of department out of 1100 identified in the study. Structural equation modeling using PLS 2.0 M3 reports significant relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…A prior study by Blenker et al (2012) indicates that there has been a remarkable increase in the number of entrepreneurship courses which support a cultural shifting in Western countries. Supporting this fact, policymakers have also provided an academic focus to enhance cultural involvement in the educational organization (Khalid et al, 2019). One aspect of this cultural influence looks for the number of educational institutions that teach entrepreneurship courses (Farny et al, 2016).…”
Section: Entrepreneurial Culturementioning
confidence: 99%
“…A prior study by Blenker et al (2012) indicates that there has been a remarkable increase in the number of entrepreneurship courses which support a cultural shifting in Western countries. Supporting this fact, policymakers have also provided an academic focus to enhance cultural involvement in the educational organization (Khalid et al, 2019). One aspect of this cultural influence looks for the number of educational institutions that teach entrepreneurship courses (Farny et al, 2016).…”
Section: Entrepreneurial Culturementioning
confidence: 99%
“…Previous research scholars have depicted that organizations benefit from their capacity and intention to take risks and adoption of newer ideas and technology in the implementation of business process that seek to introduce innovativeness for gaining competitive advantage. Various studies have reported significant entrepreneurial prospects as organizations strive to boost their performance through operational settings by introducing innovation and creativity (Khalid, Ahmed, Tundikbayeva, & Ahmed, 2019;Umrani et al, 2016).…”
Section: Objective Of the Studymentioning
confidence: 99%
“…According to Axtell et al, (1997), high levels of training transfer were noticed from trainees who perceived higher training utility. Accordingly, the urgent training needs also influenced perceptions regarding the learning transfer (Khalid, Ahmed, Tundikbayeva & Ahmed, 2019;Lim & Morris, 2006).…”
Section: Perceived Utilitymentioning
confidence: 99%